2022
DOI: 10.1097/tp.0000000000004441
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Management of Chronic Postsurgical Pain and Persistent Opioid Use Following Solid Organ Transplantation: Experiences From the Toronto General Hospital Transitional Pain Service

Abstract: Background. With >700 transplant surgeries performed each year, Toronto General Hospital (TGH) is currently one of the largest adult transplant centers in North America. There is a lack of literature regarding both the identification and management of chronic postsurgical pain (CPSP) after organ transplantation. Since 2014, the TGH Transitional Pain Service (TPS) has helped manage patients who developed CPSP after solid organ transplantation (SOT), including heart, lung, liver, and renal transplants. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Some studies have indicated that TPS is effective in alleviating postoperative pain and in reducing opioid use after discharge [107,108]. Recent reports also suggest that implementing TPS for various surgical patients resulted in a substantial reduction in the severity of CPSP and opioid consumption after discharge [109][110][111][112]. Moreover, implementing TPSs is expected to be economically feasible by reducing the social costs associated with CPSP, such as loss of productivity and treatment expenses [113].…”
Section: Tpsmentioning
confidence: 99%
“…Some studies have indicated that TPS is effective in alleviating postoperative pain and in reducing opioid use after discharge [107,108]. Recent reports also suggest that implementing TPS for various surgical patients resulted in a substantial reduction in the severity of CPSP and opioid consumption after discharge [109][110][111][112]. Moreover, implementing TPSs is expected to be economically feasible by reducing the social costs associated with CPSP, such as loss of productivity and treatment expenses [113].…”
Section: Tpsmentioning
confidence: 99%
“…Yu et al also performed a retrospective cohort study that instituted a multidisciplinary team incorporating psychology and psychotherapy as key parts of the multimodal pain management regimen [24 ▪▪ ]. They identified two subsets of patients at risk of developing CPSP thought to benefit from the multidisciplinary approach: those identified with preoperative chronic pain/opioid use and those identified after transplant with pain or opioid requirements outside of the normal trajectory.…”
Section: Multimodal Pain Managementmentioning
confidence: 99%
“…Several reports evaluated chronic opioid consumption before and after transplantation and its impact on mortality. [4][5][6] Chuan et al 10 performed a retrospective analysis of 140 SOT patients followed by a transitional pain service (TPS) at the Toronto General Hospital that provides a multidisciplinary care pathway preoperatively and postoperatively. Opioid consumption calculated in milligram morphine equivalent (MME) per day was the main outcome measure.…”
mentioning
confidence: 99%
“…The study by Chuan et al 10 has the merit to address the beneficial issue on transplant patients of a long follow-up by a specialized pain care service. Despite that, currently, some centers have a pain care referent or department, often run by an anesthesiologist or addictologist, and few are dedicated to long-term follow-up of SOT recipients.…”
mentioning
confidence: 99%
See 1 more Smart Citation